Teknik Pengambilan Keputusan Dalam Menentukan Model Manajemen Pendidikan Menengah - Muhdi, Muhdi; Kastawi, Nurkolis Siri; Widodo, Suwarno (Kelola: Jurnal Manajemen Pendidikan, 2017)
The main problem in this research is how the model of secondary education management in Central Java Province. Issues divided into a) what are the expectations of various parties regarding the transfer of secondary education management, b) how are the challenges of various parties related to the transfer of secondary education management, and c) which management model is most effective for managing secondary education in Central Java Province. This research is descriptive qualitative. Data collection through FGD was recorded with video and government policies related to secondary education. The number of informants is nine people. Research data is processed using qualitative research software, NVivo 11 Plus for Windows. The study was conducted over three months from October to December 2016. The results were a) some expectations: improving the quality of education, improving access and equity of education, improving teacher welfare and promoting professionalism. teacher; b) some of the challenges faced: the province will ignore the welfare of non-civil servant teachers and reduce the free education of secondary education; c) the most effective model is co-administration. It is recommended that the government immediately make government regulations on the management of secondary education. At the provincial level was directly made education policy. East Java provincial government has now chosen alternative "based region" in six regions of former residency in Central Java. This alternative needs to be tested for its effectiveness, if it is not effective then it is advisable to use co-administration.